Binding of [(dien)PtCl] Cl to poly(dG-dC)-poly(dG-dC) facilitates the B goes to Z conformational transition. - Ushay, H M (1982)
Chlorodiethylenetriamineplatinum(II) chloride, [(dien)PtCl]Cl, bound to less than or equal to 10% of the nucleotide bases of poly(dG-dC) . poly(dG-dC) reduces the amount of ethanol necessary to bring about the B goes to Z conformational transition in proportion to the amount of platinum complex bound as monitored by CD spectroscopy. The transition may be effected by 25% ethanol with 9.3% of the bases modified polymer an ethanol with 5.4% of the bases modified. With an unmodified polymer an ethanol concentration of 55-60% is necessary to bring about the transition. The assignment of the Z conformation was supported by 31P NMR spectroscopy. This covalent modification of the DNA is reversed by treatment with cyanide ion after which the normal amount of ethanol is necessary to achieve the transition. The platinum complex shows no enhanced binding to DNA in the Z versus the B conformation. Between 20 and 33% (saturation binding) modification, [(dien)PtCl]Cl binds cooperatively to the heterocopolymer as judged by CD spectroscopy. At this high level of modification it is no longer possible to induce the Z DNA structure with ethanol. When [(dien)PtCl]Cl is bound to preformed (with ethanol) Z DNA at saturating levels the CD spectrum is altered but reverts to the spectrum of highly modified DNA upon removal of ethanol. The antitumor drug cis-diaminedichloroplatinum(II), cis-DDP, binds to poly(dG-dC) . poly(dG-dC) and alters the CD spectrum. It does not facilitate the B goes to Z conformational change, however, and actually prevents it from happening even at very high ethanol concentrations.